Effects of environmental factors on soil organic carbon under natural or managed vegetation restoration - Hu, Pei‐Lei; Liu, Shu‐Juan; Ye, Ying‐Ying; Zhang, Wei; Wang, Ke‐Lin; Su, Yi‐Rong (Land degradation & development, 2018)
To expand the scientific understanding of soil organic carbon (SOC) accumulation in restored ecosystems, we used 246 soil samples from a rocky catchment (10.24 km2) in an ecologically fragile karst area of southwest China and measured the effects of environmental factors under different vegetation restoration types (managed, including forage grassland and plantation forest, or natural, including grassland, shrubland, and secondary forest) on soil organic carbon content (SOCC) and soil organic carbon density (SOCD). Significantly higher SOCC and SOCD were found in natural vegetation than in managed vegetation and tillage land but no differences in SOCC or SOCD were detected between managed vegetation and tillage land. The environmental factors include rock outcrop ratio (ROR), bulk density, altitude, soil depth, slope gradient, and pH, all showing significant effect on SOC. The proportion of variations in SOCC and SOCD explained by environmental factors was higher in natural vegetation restoration than in managed vegetation restoration, and this proportion increased along the successional gradient. However, the environmental factors driving variations in SOCC and SOCD differed according to vegetation type. Soil bulk density had the strongest effect on SOCC variation in all vegetation types, except for forage grassland, in which the variation was instead controlled by ROR. The variation of SOCD was mainly driven by ROR in most vegetation types, except for tillage land and forage grassland, in which the driving factor was altitude. This results indicated that natural vegetation restoration is more beneficial to SOC sequestration than managed vegetation restoration and thus for mitigating global climate change. Accordingly, future studies should take these different environmental drivers under different vegetation restoration types into consideration when modeling SOC and guiding restoration management.